Whether socioeconomic status matters in accessing residential college: role of RC in addressing academic achievement gaps to ensure sustainable education - Gui, Pingping; Alam, Gazi Mahabubul; Hassan, Aminuddin (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Following the fourth objective of the United Nations’ Sustainable Development Goals (SDGs), education disparities are one of the most serious issues holding back national development. Despite efforts being made to tackle this discrepancy, it has long been a source of concern for many communities. It is important to note that residential colleges (RCs) have evolved and contributed to higher education for several decades now, aiming to provide an equal and inclusive living and learning environment. Having said that, while disparity is still one of the most challenging issues in this system, it has not been fully examined. Using stratified random sampling on RC students’ data from undergraduate universities piloting RC programs up to 2018 in different parts of China, this study examines the effects of socioeconomic status (SES) on RC access. The study further explores the difference in academic achievement among RC students from diverse SES backgrounds and comprehensively analyzes the impact of RC on sustainable education. The study finds that disparities exist in accessing RC for individuals from varied SES backgrounds. However, RC mitigates the influence of SES on academic achievement to curtail these differences. The findings imply that ensuring access to RC for individuals from underprivileged SES backgrounds should be prioritized to address education-disparity-related challenges.